Davis's drug guide for nurses - Deglin, Judith Hopfer; Vallerand, April Hazard (Philadelphia : F.A. Davis, 2007)
"This new 10th edition of Davis's Drug Guide for Nurses has the latest FDA approvals and a stronger emphasis on vulnerable populations including expanded pediatric coverage with new indications and dosing recommendations for the 100 top pediatric drugs. From pediatrics to geriatrics and from pregnancy to breast-feeding considerations, Davis's Drug Guide for Nurses addresses the entire life span." "Includes: expanded coverage for Peds, OB, and Geri gives you the most comprehensive drug information for vulnerable populations across the life span; a special highlighted tab identifies High Alert medications, and information throughout the monograph explains what you can do to ensure patient safety; "Do not confuse with" and "Do not crush, break, or chew" caution statements highlighted in color support safe practice; and side effects organized by body systems with the most frequent problems underlined and life-threatening problems capitalized and in color."--BOOK JACKET.
Keywords: Drugs -- Handbooks, manuals, etc; Nursing -- Handbooks, manuals, etc; Clinical pharmacology -- Handbooks, manuals, etc; Pharmaceutical Preparations -- administration & dosage -- Handbooks; Drug Therapy -- nursing -- Handbooks; Pharmacology, Clinical -- methods -- Handbooks